2012
DOI: 10.1073/pnas.1209793110
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Carnobacterium spp. from permafrost under low pressure, temperature, and anoxic atmosphere has implications for Earth microbes on Mars

Abstract: The ability of terrestrial microorganisms to grow in the near-surface environment of Mars is of importance to the search for life and protection of that planet from forward contamination by human and robotic exploration. Because most water on present-day Mars is frozen in the regolith, permafrosts are considered to be terrestrial analogs of the martian subsurface environment. Six bacterial isolates were obtained from a permafrost borehole in northeastern Siberia capable of growth under conditions of low temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 26 publications
4
66
0
Order By: Relevance
“…Results demonstrate that at least one terrestrial microorganism can grow under hypobaric conditions relevant to the surface of Mars. In a parallel study, Nicholson et al (2012) demonstrated growth of eight type strains and two Siberian permafrost field strains in the genus Carnobacterium in 7 mbar, 0°C, and CO 2 -enriched anoxic atmospheres. Thus, at least 11 species of bacteria in two genera appear capable of growth under hypobaric conditions relevant to Mars.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrate that at least one terrestrial microorganism can grow under hypobaric conditions relevant to the surface of Mars. In a parallel study, Nicholson et al (2012) demonstrated growth of eight type strains and two Siberian permafrost field strains in the genus Carnobacterium in 7 mbar, 0°C, and CO 2 -enriched anoxic atmospheres. Thus, at least 11 species of bacteria in two genera appear capable of growth under hypobaric conditions relevant to Mars.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies on permafrost bacterial growth and metabolism have focused on temperatures at or above 0 1C, assuming that metabolic activity predominantly occurs when permafrost soils have thawed (Martineau et al, 2010;Liebner et al, 2011;Mackelprang et al, 2011;He et al, 2012;Nicholson et al, 2013). However, the concept that bacterial activity in frozen soils can also have a major role in biogeochemical cycles is changing (Bergholz et al, 2009;McMahon et al, 2009;Vishnivetskaya et al, 2009;Mykytczuk et al, 2012;Tveit et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this is also the lower limit of pressure before significant decreases in growth rate and colony size were demonstrated in a number of Gram-positive and Gram-negative bacterial species (10,11,29,31). Therefore, it appears for most bacteria (with a few notable recent exceptions mentioned above [10,11]) that there exists a low-pressure limit at ϳ10 kPa, below which cellular processes begin to be inhibited and the GSR is induced in B. subtilis. As observed previously with other environmental stresses (ethanol, heat, high salt), the SigB-mediated GSR does not seem to be required for growth at 5 kPa.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a lack of natural LP environments on the Earth's surface, knowledge of the microbiology of LP environments is gaining importance due to (i) the increasing use of hypobaric chambers for long-term storage of high-value perishable agricultural commodities (5), (ii) the sampling of microbes in the limits of the upper atmosphere (4,(6)(7)(8)(9), and (iii) the astrobiological implications of terrestrial microorganisms capable of living in extreme LP environments, such as those found on Mars (10,11).…”
mentioning
confidence: 99%